Deciphering the interplay between cysteine synthase and thiol cascade proteins in modulating Amphotericin B resistance and survival of Leishmania donovani under oxidative stress - Kuljit Singh; Vahab Ali; Krishn Pratap Singh; Parool Gupta; Shashi S. Suman; Ayan K. Ghosh; Sanjiva Bimal; Krishna Pandey; Pradeep Das (Redox Biology, 2017)
Leishmania donovani is the causative organism of the neglected human disease known as visceral leishmaniasis which is often fatal, if left untreated. The cysteine biosynthesis pathway of Leishmania may serve as a potential drug target because it is different from human host and regulates downstream components of redox metabolism of the parasites; essential for their survival, pathogenicity and drug resistance. However, despite the apparent dependency of redox metabolism of cysteine biosynthesis pathway, the role of L. donovani cysteine synthase (LdCS) in drug resistance and redox homeostasis has been unexplored. Herein, we report that over-expression of LdCS in Amphotericin B (Amp B) sensitive strain (S1-OE) modulates resistance towards oxidative stress and drug pressure. We observed that antioxidant enzyme activities were up-regulated in S1-OE parasites and these parasites alleviate intracellular reactive oxygen species (ROS) efficiently by maintaining the reduced thiol pool. In contrast to S1-OE parasites, Amp B sensitive strain (S1) showed higher levels of ROS which was positively correlated with the protein carbonylation levels and negatively correlated with cell viability. Moreover, further investigations showed that LdCS over-expression also augments the ROS-primed induction of LdCS-GFP as well as endogenous LdCS and thiol pathway proteins (LdTryS, LdTryR and LdcTXN) in L. donovani parasites; which probably aids in stress tolerance and drug resistance. In addition, the expression of LdCS was found to be up-regulated in Amp B resistant isolates and during infective stationary stages of growth and consistent with these observations, our ex vivo infectivity studies confirmed that LdCS over-expression enhances the infectivity of L. donovani parasites. Our results reveal a novel crosstalk between LdCS and thiol metabolic pathway proteins and demonstrate the crucial role of LdCS in drug resistance and redox homeostasis of Leishmania. Keywords: Leishmania, Cysteine synthase, Drug resistance, Thiol metabolism, Oxidative stress, Amphotericin B, Trypanothione